ENERGY MODELS OF THE BOUNDARIES OF BLOCKS OF THE GEOLOGICAL AND GEOPHYSICAL MEDIUM - Tsarev V.P. (My University, 1989)
Recently, attempts were made to develop a quantitative theory of the geological and geophysical medium i.e., in situ methods for determining the properties of rocks and of the processes taking place in them. Obtaining such data is the main objective of earth science, and the importance of such information for geology, geophysics, geochemistry and other subdisciplines can hardly be over-estimated. A discrete geological and geophysical medium, the model of M.A. Sadovskiy et al. contains component parts, namely boundary zones of blocks of all structural hierarchical levels. They exhibit the ability to store, transform, amplify, and emit the energy of sources that are internal and external with respect to the system, as well as to dissipate this energy or transform it into other forms, among them the energy of the chemical bond.